Nobility or Financial Sustainability? - T., Senthil Kumar (The International Journal Research Publications, 2016)
This article attempts to provide an uncomplicated view on two important notions in Finance viz. Profit and Cash Flow. The significance of maintaining ‘reasonable’ profit level and ‘adequate’ cash flows have been explained using common sociological and physiological examples. Further, it is argued that the firms ought to have followed the notion of sustainability, i.e. People, Planet and Profit, all along.